Human memory the general theory and its various models - Malmberg, Kenneth J. (Cambridge University Press, 2025)
The General Theory of human memory is the most prominent result of the cognitive revolution in psychology. Despite its role in modern memory research, the General Theory is not well understood. This book describes the General Theory of human memory and applies it to numerous empirical phenomena. It details the prominent architectures for formally modeling the flow of information among the proposed memory structures using the search of associative memory (SAM) and the retrieving effectively from memory (REM) models
Title from publisher's bibliographic system (viewed on 17 Jan 2025)
Introduction -- Models of cognitive control, storage, and retrieval -- Search and detection -- Sequential effects -- Forgetting -- Differentiation -- Knowledge -- Modeling the consequences of testing memory -- The Buffer model revisited -- Acknowledgements -- Index
Keywords: Memory; Memory / Study and teaching